Investigation on the surface finish, MRR and the surface damage during the EDM of tungsten carbide - Khan, Ahsan Ali; Abdulkareem, Suleuman; Ahmad Abdul Ghani, Nadiatul Amirah; Mohammad Ariffin, Dayanna Sarah (Trans Tech Publications, Switzerland, 2011)
EDM is a nontraditional method of removing material by a series of rapidly recurring electric discharges between an electrode (the cutting tool) and the workpiece, in a medium of a dielectric fluid. EDM is a precision machining technique and is used in making dies and molds of extremely hard materials that cannot be machined by conventional techniques. The present work was conducted in order to investigate the surface finish, material removal rate and the surface damage during EDM. Copper and carbide were taken as the electrode and the work materials for the present study. The influence of current and pulse-on time on the responses were studied. Design of Experiment (DOE) was used to conduct the investigation. It was found that MRR and surface roughness increases with both current and pulse on time. Tool wear, work surface damage and materials migration between the electrode and the workpiece was found to be increased with current.